The effects of driving patterns and PEM fuel cell degradation on the lifecycle assessment of hydrogen fuel cell vehicles. (29th January 2020) - Ahmadi, Pouria; Torabi, Seyed Hosein; Afsaneh, Hadi; Sadegheih, Yousef; Ganjehsarabi, Hadi; Ashjaee, Mehdi
Abstract: This research paper mainly deals with the realistic simulation of hydrogen fuel cell vehicles and the development of a lifecycle assessment (LCA) tool to calculate and compare the environmental impacts of hydrogen fuel cell passenger vehicles with conventional vehicles. Since fuel cell vehicles are equipped with regenerative braking, they have strong potential to recover an ample portion of the energy being wasted in the braking system. Thus, the driving cycle can significantly affect the performance of fuel cell vehicles. In order to investigate the effect of driving patterns, several driving patterns are considered, and both vehicle fuel economy and lifecycle emissions are calculated and compared. Fuel cell degradation, on the other hand, is another major problem fuel cell vehicles face. This is mainly caused by the starts/stops, acceleration/deceleration, membrane humidity variation and a high load of the engine. When the vehicle operates on various driving patterns, the fuel cell will degrade which eventually affects the fuel economy. The effect of fuel cell degradation is also investigated for these driving patterns, and the results are compared. The results showed that the highway driving cycle has the lowest total lifecycle emission compared to New York city driving cycle, the city of Surrey (CoS) driving cycle, and the UDDS driving cycles. The results also indicate that fuel cell degradation undesirably affected the average fuel economy of the vehicle for about 23%. Highlights: Developing a customized LCA tool for comparison of Hydrogen vehicle with gasoline. To consider the vehicle specification and real world driving cycle. To see the effect of fuel cell degradation on lifecycle emission. To see the effect of driving patterns on both fuel economy and emission.